2006
DOI: 10.1007/s00436-006-0344-3
|View full text |Cite
|
Sign up to set email alerts
|

A cathepsin L-like cysteine proteinase gene from the protozoan parasite, Cryptobia salmositica

Abstract: The present study describes the identification of a cathepsin L-like cysteine proteinase gene (CYS) from the hemoflagellate Cryptobia salmositica. Genomic DNA sequence of cysteine proteinase was obtained by genome walking using degenerate primers. Specific primers were designed to amplify the cDNA of cysteine proteinase from mRNA by rapid amplification of cDNA ends-PCR. The open reading frame of CYS is 1,329 bp, with 443 deduced amino acids. Based on the sequence analysis, cysteine proteinase of C. salmositica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The characteristics of the peptidase proteins, including frequency, protein length, homology to previously deposited proteins and conserved domains are shown in Table  1. The conserved domains were analyzed using the SMART web program, Genbank BLAST program, and other literature [16-22]. …”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the peptidase proteins, including frequency, protein length, homology to previously deposited proteins and conserved domains are shown in Table  1. The conserved domains were analyzed using the SMART web program, Genbank BLAST program, and other literature [16-22]. …”
Section: Resultsmentioning
confidence: 99%
“…and Trypanosoma spp. (Jesudhasan et al 2007a), while the metallopeptidase was shown to share homology with the major surface metallopeptidase from Leishmania spp. (Jesudhasan et al 2007b).…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, the metalloprotease and cysteine protease genes of C. salmositica were sequenced [45, 46] and inserted into plasmid vectors (pEGFP-N) to produce a metalloprotease-plasmid vaccine and a cysteine-plasmid vaccine [47]. Rainbow trout and Atlantic salmon, Salmo salar , injected intramuscularly with the metalloprotease-plasmid vaccine consistently had lower packed cell volume (as metalloprotease was secreted into the blood) than controls (fish inoculated either with plasmid alone or with cysteine-plasmid vaccine) at 2–4 wpv.…”
Section: Strategies Against Cryptobia and Cryptobiosismentioning
confidence: 99%